PENYULUHAN PENINGKATAN LITERASI INFORMASI DI GRIYA YATIM DHUAFA YOGYAKARTA - setianingsih, wita (Buletin Udayana Mengabdi, 2020)
The purpose of Community Service at Griya Yatim Dhuafa is to increase the literacy of information about the service participants. This community service activity was attended by 30 participants with a junior high school education background. Community service activities at Griya Yatim Dhuafa Yogyakarta in the form of counseling and discussions with the target audience in order to foster increased competency of participants in literacy of information originating from the internet. From the results of the questions and answers and discussions carried out an evaluation of the activity, whether the participants increased their understanding or not. Besides being given oral questions at the beginning and end of the activity as an evaluation also given written tests. The conclusion of the implementation of community service activities can foster social relations to the community, in this case the target community is administrators and foster children, can apply knowledge in Higher Education to the community through counseling materials about the ability of literacy in addressing information from the internet, can participate in educating the life of the nation by providing additional insight, knowledge and understanding in responding to and criticizing various information that is easily obtained through the internet, especially information, the ability of information literacy that comes from the internet of community service participants increases with the existence of this community service activity.